1999
DOI: 10.1258/0956462991914276
|View full text |Cite
|
Sign up to set email alerts
|

Short-term follow up of cervical squamous intraepithelial lesions associated with HIV and human papillomavirus infections in Africa

Abstract: A prospective study in gynaecology clinics was conducted in Abidjan, Côte d'Ivoire, to assess the short-term evolution of squamous intraepithelial lesions (SILs). Of 94 women with a cytological diagnosis of SIL, 38 were infected with HIV. The average follow-up period after the initial smear was 5 months. Detection of human papillomavirus (HPV) by polymerase chain reaction (PCR) was performed at both the time of enrolment and final follow-up smear. There were 39 cases of persistent SILs. HIV-positive women had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Two studies followed women with ASCUS at baseline 33,34 , finding a rate of 13.7 cases of SIL per 100 women-years and 3.2 cases of HSIL per 100 women-years. Study cumulative risks, though not comparable between studies, were higher for HIV-positive participants than for HIV-negative participants in all five studies that included both populations 10,33,35,37,39 .…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Two studies followed women with ASCUS at baseline 33,34 , finding a rate of 13.7 cases of SIL per 100 women-years and 3.2 cases of HSIL per 100 women-years. Study cumulative risks, though not comparable between studies, were higher for HIV-positive participants than for HIV-negative participants in all five studies that included both populations 10,33,35,37,39 .…”
Section: Resultsmentioning
confidence: 76%
“…Four of the studies were conducted in the USA 3336 , 4 in the European Union with one including women from France and French Guiana 7,10,37,38 , 2 in Africa 28,39 , and 1 in Brazil. No studies came from Asia, Australia, Central America, or Eastern Europe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, HIV-positive women have been shown to have both higher rates of CIN prevalence and of low-grade lesion persistence 43,44 . One recent report has even provided a biological mechanism for increased cervical carcinogenesis via HIV infection through the mediation of COX-2 expression, a molecule linked to cervical carcinogenesis 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In sub-Saharan Africa, for instance, where two thirds of the world's HIV-infected population live, HPV types vary by country and HIV status and differ significantly from HPV types seen in other regions of the world, possibly in part due to geographic and genetic variation in HLA haplotypes [1115]. Multiple prospective studies have demonstrated that women with HIV infection are much more likely than HIV-negative women to have persistent HPV, often with oncogenic subtypes [1618]. It has been estimated that a vaccine against HPV types 16 and 18 would theoretically prevent 71% of cervical cancers worldwide, but would preferentially favor Asia and North America over Africa and South America [14].…”
Section: Introductionmentioning
confidence: 99%